The Teaching Performance of the Teachers in Online Classes: A Sentiment Analysis of the Students in a State University in the Philippines - Asgar D. Mamidted; Saima Sansaluna Maulana (RIRAI Publisher, 2023)
Understanding the factors that influence students' perceptions may also assist administrators in making informed decisions about course and organizational design, as well as guiding professional development workshops for instructors. The goal of this sentiment analysis was to describe students' opinions about teachers' teaching performance in online classes. It sought to ascertain the most frequently occurring words in relation to their sentiments, as well as the emerging clusters derived from their sentiments. This study used a descriptive qualitative method employing sentiment analysis of Orange text mining software. Sentiment analysis extracts information from positive and negative words in text, from the context of those words, and from the linguistic structure of the text. The 237 college students were the participants of this study. The findings show that the emerging clusters derived from the sentiments of the students were the teachers facilitate learning and motivate students to learn. Teachers act as facilitator and motivator of students to learn in online classes. The teaching performance of the teachers can be manifested in how they facilitate the teaching-learning process and how they give feedbacks and motivations to students. Consequently, the teaching performance of the teachers in online classes is one of the indicators of the students’ sentiments. This implied that, once the teacher performed very well in the class, students become satisfied and perform better in the class.